A study on customer satisfaction towards service quality provide by State Procurement Sabah / Shelbeth Ann Malison - Malison, Shelbeth Ann (2009)
The benefit of good customer satisfaction on business as well as the costs of poor customer satisfaction have been clearly demonstrated in the research literature. The 5 dimension of Customer Satisfaction is based on the company that quality can be defined by the differences between the customer and the organization on the perceptions, expectations, and actual delivery of service. These 5 dimension model provide information that can be used to identify the relative strengths and weaknesses of the processes and components of service. In turn, the business is able to implement adjustments in service delivery that directly improve customer satisfaction and profit. SERVQUAL, an instrument based on this model, has been utilized in various service industries with mixed results. The purpose of this study was to develop the internal customer satisfaction survey for a private human service agency and collect data from both internal and external external sources. A modified version of SERVQUAL being ask by questionnaire. The respondent was the internal customer of State Procurement Sabah. Internal customer of State Procurement Sabah are the other employees from the other department or division at Telekom Malaysia Berhad office. Internal respondent differed in the rank order of importance of the service dimensions. Possible explanations for these results, similarities and differences of previous research, and problems with the study are discussed. The study concludes with recommendations for the Company especially for State Procurement Sabah division.